Trust and empowerment of employees in organizations public and private in Lima - Loli P., Alejandro (2017)
This study aims to understand the relationship between organizational trust and empowerment of employees in public and private organizations of Lima. Using two questionnaires measuring variables in a sample of 327 professionals from various specialties who complete postgraduate studies (second specialty, masters and doctorate) in a public university, it was found that there is a high degree of trust and empowerment among the participants about their position in the organization where they work; and both variables are associated significantly and positively. An analysis to determine the importance of population and organizational behavior variables sample indicates that there is very weak differences in the relationship among trust, gender,marital status and any other; whereas there is no relationship among empowerment and demographic or organizational variable, they are independent variables.